Profesionalitas Guru MAN 2 Model Medan - Almaajid, Rizqi; Siregar, Nurjannah; Pradita, Syakila; Husna, Malika Aulia; Amanda, Tiara; Sagala, Ardin Rizki (Yayasan Pendidikan Islam Akmalia, 2022)
In general, this study is intended to describe the role of teacher professionalism in education in schools. The specific purpose of this research is to describe the professionalism of teacher performance in improving education in schools at the madrasah education level at MAN 2 MODEL MEDAN. Mini research activities on the role of teacher professionalism in Education at the MAN 2 MEDAN MODEL School is carried out using the interview method or qualitative descriptive method. The results of the research, the role of teacher professionalism in education in schools is related to how to become a professional teacher in accordance with the assessment of national education in Indonesia. The professionalism of teachers in each school is different. depending on the qualifications of the school. So it can be concluded that the role of teacher professionalism is very influential in the development of education in a school.